Musa Champa Fruit Peel Ash: A Renewable And Highly Effective Heterogeneous Base Catalyst For Biodiesel Production From Linum Usitatissimum (Linn.) (Flaxseed) Oil As A Source - Dutta, Trisha; Saikia, Monmi; Nandi, Swapna; Narzary, Raju; Brahma, Ashok Kumar; Basumatary, Hiu (Metallurgical and Materials Engineering, 2025)
The use of a biomass-derived catalyst for bio-diesel production has gained attention today. The heterogeneous catalyst derived from the fruit peel of Musa champa fruit, a waste biomass material, was a highly efficacious catalyst for biodiesel manufacture. The present work reveals catalytic activities of varying catalyst loading; prepared from the fruit peel of Musa champa and applied in biodiesel production from Linum usitatissimum (Linn.) oil, commonly known as flax seed. The ash of Musa champa (MCA) fruit peel, which has a good content of potassium, demonstratedthe greatest level of catalytic activity. The catalyst has been characterized by FTIR, FESEM, and TGA analysis. Conversion of oil to bio-diesel was confirmed by NMR and GC-MS techniques. This low-cost and environmentally benign catalyst claims a novel procedure for the manufacture of bio-diesel from Linum usitatissimum (Linn.) oil.